Osteoblast Progenitors Enhance Osteogenic Differentiation of Periodontal Ligament Stem Cells. Issue 10 (1st October 2017) - Yu, Miao; Wang, Limei; Ba, Pengfei; Li, Linxia; Sun, Long; Duan, Xiaoqi; Yang, Pishan; Yang, Chengzhe; Sun, Qinfeng
Abstract : Background: Osteoblasts and periodontal ligament stem cells (PDLSCs) play an important role in maintaining physiologic function of periodontal tissues and participating in periodontal regeneration. Elucidation of interactions between osteoblasts and PDLSCs will aid understanding of periodontal regeneration mechanisms. This study aims to determine whether preosteoblasts can promote osteoblastic/cementoblastic differentiation of PDLSCs. Methods: PDLSCs were cultured alone (control group), or cocultured indirectly with human gingival fibroblasts (HGFs) (HGFs group) or MC3T3‐E1 cells (OB groups). Alkaline phosphatase (ALP) activity and gene/protein expressions levels of ALP, runt‐related transcription factor‐2, and osteopontin (OPN) were assessed. Cementum attachment protein and cementum protein 23 messenger RNA expressions were also evaluated. Bone morphogenetic protein (BMP)‐2 secreted by HGFs/MC3T3‐E1 cells was assessed by enzyme‐linked immunosorbent assay. Extracellular matrix calcification was measured by staining to quantify calcium content. Results: ALP activity and gene/protein expression levels of osteogenic markers were significantly higher in the OB groups compared with the HGFs and control groups. Optimal enhancement of these parameters occurred at cell ratios of 2:1 to 1:1 (MC3T3‐E1:PDLSCs). Mineralized nodule formation and calcium content were significantly increased in the OB groups compared with the HGF and control groups. The greatest improvement took place at the 2:1 (MC3T3‐E1:PDLSCs) seeding ratio. BMP‐2 from MC3T3‐E1‐conditioned medium was significantly and time‐dependently increased compared with that from HGF ‐ conditioned medium. Conclusion: Preosteoblasts can indirectly enhance the osteoblastic/cementoblastic differentiation and mineralization of PDLSCs with an optimal preosteoblasts:PDLSCs ratio in the range of 2:1 to 1:1.